Neoadjuvant pembrolizumab-carboplatin-paclitaxel in locally advanced squamous cell carcinoma of the oral cavity: A case report and literature review - Abdulrahman Hesham; Fawaz AlOtaibi; D. David Kim; Yousef Alshamrani; Joao Hyppolito; Katie Jubala (Oral Oncology Reports)
Head and neck cancers are being diagnosed more frequently in elderly patients and at advanced stages. In these cases, standard treatment methods are often not feasible due to patient frailty and malnutrition. A few trials have demonstrated the safety and effectiveness of immune checkpoint inhibitors (ICIs) as neoadjuvant therapy for locally advanced oral cancer. We present the case of a 51-year-old male patient who had locally advanced oral cavity cancer that was treated with the combination of pembrolizumab and weekly carboplatin and paclitaxel. This treatment resulted in a major pathological response, leading to a significant reduction in tumor size and allowing for surgical treatment. In addition, the patient remains free of locoregional disease nine months after the surgery. Clinical trials are essential to investigate the viability of this potentially less toxic and more convenient combined therapy in patients with advanced squamous cell carcinoma of the oral cavity.